Arbovirus infection in Aedes aegypti from different departments of Colombia - Gómez, Marcela; Martínez, David; Hernández, Carolina; Luna, Nicolás; Patiño, Luz Helena; Bohórquez Melo, Ramiro; Suarez, Luis Alejandro; Palma-Cuero, Mónica; Murcia, Luz Mila; González Páez, Leonel; Estrada Bustos, Leonardo; Medina, Manuel Alfonso; et al. (Frontiers in Ecology and Evolution, 2022)
The lack of precise and timely knowledge about the molecular epidemiology of arboviruses of public health importance, particularly in the vector, has limited the comprehensive control of arboviruses. In Colombia and the Americas, entomovirological studies are scarce. Therefore, this study aimed to describe the frequency of natural infection and/or co-infection by Dengue (DENV), Zika (ZIKV), and Chikungunya (CHIKV) in Aedes spp. circulating in different departments of Colombia (Amazonas, Boyacá, Magdalena, and Vichada) and identifying vector species by barcoding. Aedes mosquitoes were collected in departments with reported prevalence or incidence of arbovirus cases during 2020-2021, located in different biogeographic zones of the country: Amazonas, Boyacá, Magdalena, and Vichada. The insects were processed individually for RNA extraction, cDNA synthesis, and subsequent detection of DENV (serotypes DENV1-4 by multiplex PCR), CHIKV, and ZIKV (qRT-PCR). The positive mosquitoes for arboviruses were sequenced (Sanger method) using the subunit I of the cytochrome oxidase (COI) gene for species-level identification. In total, 558 Aedes mosquitoes were captured, 28.1% (n=157) predominantly infected by DENV in all departments. The serotypes with the highest frequency of infection were DENV-1 and DENV-2 with 10.7% (n=58) and 14.5% (n=81), respectively. Coinfections between serotypes represented 3.9% (n=22). CHIKV infection was detected in one individual (0.2%), and ZIKV infections were not detected. All infected samples were identified as A. aegypti (100%). From the COI dataset (593 bp), high levels of haplotype diversity (H=0.948±0.012) and moderate nucleotide diversity (π=0.0225±0.003) were identified, suggesting recent population expansions. Constructed phylogenetic analyses showed our COI sequences' association with lineage I, which was reported widespread and related to a West African conspecific. We conclude that natural infection in A. aegypti by arbovirus might reflect the country's epidemiological behavior, with a higher incidence of serotypes DENV-1 and DENV-2, which may be associated with high seroprevalence and asymptomatic infections in humans. This study demonstrates the high susceptibility of this species to arbovirus infection and confirms that A. aegypti is the main vector in Colombia. The importance of including entomovirological surveillance strategy within public health systems to understand transmission dynamics and the potential risk to the population is highlighted herein.